Satisfaction Comparison of Binocular Distant Vision and Monovision in Higher-Order Aspheric Intraocular Lens Eyes - Mizumoto, Kyoichi; Terao, Haruka; Kamei, Motohiro; Oka, Yusuke (JAPANESE ORTHOPTIC JOURNAL, 2024)
【Purpose】Patients inserted with high-order aspheric intraocular lenses TECNIS Eyhance® (TE) were divided into the binocular distance vision (BV) and monovision (MV) groups, and their satisfactions in the postoperative daily life were compared. 【Subjects and Methods】We retrospectively selected 59 patients who had received TE insertion in both eyes at the Aichi Medical University Hospital for at least three months and had uncorrected binocular visual acuity of 0.7 or better. The subjects with a subjective refraction difference of ≤ 0.5 D between the two eyes and those with a difference between 0.6 D and 1.5 D were respectively classified as the BV (32 patients; mean age, 71.4±8.63) and MV (27 patients; mean age, 71.0±11.0) groups. In a questionnaire survey, the subject’s satisfaction in using the uncorrected vision to perform daily life tasks including driving, walking, shopping, watching television, cooking, eating, computer use, reading, and smartphone use was scaled from 1 to 5 with 1 = “dissatisfied”, 2 = “somewhat dissatisfied”, 3 = “normal”, 4 = “somewhat satisfied”, and 5 = “satisfied”. The satisfaction levels were compared between the BV and MV groups. We conducted a multiple regression analysis with the satisfaction level as the dependent variable and gender, presence of monovision, postoperative subjective spherical equivalent power, and uncorrected binocular visual acuity at 5 m and 50 cm as the explanatory variables selected using stepwise regression. The percentages of the patients who had made glasses after surgery were also compared. 【Results】Postoperative binocular naked eye visual acuity was significantly more satisfactory for the MV group at the 30 cm and 40 cm distances. The MV group showed a significantly higher satisfaction level when performing tasks including eating, reading, and using a smartphone. With women being more satisfied, gender was the factor that affected the satisfaction level. The respective percentages of the patients who had made glasses after surgery were 78.1% and 29.6% for the BV and MV groups. 【Conclusion】After TE insertion, patients aiming for a postoperative refraction of about 1.00 D could achieve a higher satisfaction level with monovision and have a lower frequency of glasses use after surgery.